A single day of mixed-macronutrient overfeeding does not elicit compensatory appetite or energy intake responses but exaggerates postprandial lipaemia during the next day in healthy young men. Issue 8 (30th January 2019) - Deighton, Kevin; King, Andy J.; Matu, Jamie; Shannon, Oliver M.; Whiteman, Oliver; Long, Alice; Huby, Matthew D.; Sekula, Miroslav; Holliday, Adrian
Abstract: Discrete episodes of overconsumption may induce a positive energy balance and impair metabolic control. However, the effects of an ecologically relevant, single day of balanced macronutrient overfeeding are unknown. Twelve healthy men (of age 22 (sd 2) years, BMI 26·1 (sd 4·2) kg/m 2 ) completed two 28 h, single-blind experimental trials. In a counterbalanced repeated measures design, participants either consumed their calculated daily energy requirements (energy balance trial (EB): 10 755 (sd 593) kJ) or were overfed by 50 % (overfeed trial (OF): 16 132 (sd 889) kJ) under laboratory supervision. Participants returned to the laboratory the next day, after an overnight fast, to complete a mixed-meal tolerance test (MTT). Appetite was not different between trials during day 1 ( P >0·211) or during the MTT in the fasted or postprandial state ( P >0·507). Accordingly, plasma acylated ghrelin, total glucagon-like peptide-1 and total peptide YY concentrations did not differ between trials during the MTT (all P >0·335). Ad libitum energy intake, assessed upon completion of the MTT, did not differ between trials (EB 6081 (sd 2260) kJ; OF 6182 (sd 1960) kJ; P =0·781). Plasma glucose and insulin concentrations were not different between trials ( P >0·715). Fasted NEFA concentrations were lower in OF compared with EB ( P =0·005), and TAG concentrations increased to a greater extent on OF than on EB during the MTT ( P =0·009). The absence of compensatory changes in appetite-related variables after 1 d of mixed macronutrient overfeeding highlights the limited physiological response to defend against excess energy intake. This supports the concept that repeated discrete episodes of overconsumption may promote weight gain, while elevations in postprandial lipaemia may increase CVD risk.